PMO-217 Preoperative endoscopic biliary drainage and short-term clinical outcome following pancreaticoduodenectomy for pancreatic adenocarcinoma: site-specific factors. (28th May 2012) - Scott, E; Mole, D; Miller, A; Ravindran, R; Hidalgo, E; Duxbury, M
Abstract : Introduction: The role of preoperative endoscopic biliary drainage (PEBD) prior to pancreaticoduodenectomy (PD) remains controversial. We sought to determine the effects of PEBD on the short-term outcome of initially jaundiced patients undergoing PD for pancreatic adenocarcinoma in a regional Hepatopancreaticobiliary (HPB) Surgery unit. Methods: 100 consecutive initially jaundiced patients undergoing PD for histologically-confirmed pancreatic adenocarcinoma at our institution between 2006 and 2009 were identified from a prospectively maintained database. Patient demographics, perioperative serum bilirubin levels, surgical complications (Clavien classification), length of inpatient stay and in-hospital mortality were assessed. The use of PEBD, the location in which PEBD was performed, and time from PEBD to PD were ascertained. Three patient groups were defined: 1. No PEBD, 2. PEBD in HPB surgery unit (PEBD-HPB) and 3. PEBD in non-HPB surgery unit (PEBD-nHPB). Patients undergoing preoperative percutaneous biliary intervention were excluded from the study. Results: Mean patient age was 66 years (SD=11.9), M:F=56:44. 74/100 patients underwent PEBD prior to PD, of whom 53 (72%) patients underwent PEBD-HPB and 21 (28%) underwent PEBD-nHPB. In-hospital mortality did not significantly differ between the three patient groups. Mean preoperative serum bilirubin was significantly higher in No PEBD group (p<0.01). Mean length of inpatient stay and occurrence of documented infective wound complications were significantly higher in the PEBD-nHPB group vs PEBD-HPB and No PEBD groups (p=0.035). Mean time from PEBD to PD was significantly higher in the PEBD-nHPB vs the PEBD-HPB group (p=0.045). Conclusion: In this albeit small sample of patients, PEBD prior to PD did not significantly affect indicators of short-term perioperative morbidity and mortality. PEBD may be detrimental when performed in non-HPB surgical units. While increased time from PEBD to PD may play a role, the cause of this association remains to be determined. The role of PEBD prior to PD warrants further evaluation in the context of a well-designed prospective clinical trial. Competing interests: None declared.